The Character “Put On” Influence on Peranakan TiongHoa Identity through Indonesian Values - Johanes, Johanes (Gondang: Jurnal Seni dan Budaya, 2024)
"Put On" is the name of a character as well as the title of a comic that was once popular in Indonesia. Put On was published around 1931 by Kho Wan Gie in the mass media. The comic Put On showcases many aspects of Chinese Peranakan culture residing in Jakarta. The Chinese culture depicted in the comic includes language, daily habits, family structure, and the food consumed. In the comic, Put On is portrayed as a mischievous, naive, and childish character, despite being depicted as a large, middle-aged man. This research was conducted using qualitative methods in the form of multimodal analysis and narrative inquiry. Observations from the multimodal analysis method were carried out to examine the graphic narrative elements within the comic, while the narrative inquiry was conducted to gain insight into the reading experience of Put On. The aspects examined in the reading experience include character design (drawing style, physical appearance, and clothing style), language (body gestures and speech), and visualizations of social situations. The results of the research indicate that the Chinese Peranakan identity is not immediately apparent from the design and traits of Put On as the main character. However, it is through his interactions with other characters such as using distinctive language and his inhabit specifi social environments that the comic Put On successfully represents peranakan TiongHoa culture.